Histologic Findings in Captive American Horseshoe Crabs (Limulus polyphemus). Issue 6 (November 2019) - LaDouceur, Elise E. B.; Mangus, Lisa; Garner, Michael M.; Cartoceti, Andrew N.
Histopathology of 61 captive American horseshoe crabs (HSCs; Limulus polyphemus ) is reviewed. HSC organs evaluated histologically included body wall (chitin, epidermis, dermis, and skeletal muscle), hepatopancreas, gut, gonads, book gills, eyes, heart, brain, and coxal gland. In descending order, lesions were most frequently identified in compound eye, body wall, book gills, hepatopancreas, chitinous gut, nonchitinous gut, heart, and brain; lesions were not observed in coxal gland or gonads. Hemocytes (also called amoebocytes) surrounded infectious agents and occluded ulcers. Large hemocyte aggregates had a central eosinophilic coagulum (ie, hemocyte coagulum). Cutaneous ulceration (34/60 cases), branchitis (29/48 cases), and ophthalmitis (17/20 cases) were common lesions and consistently associated with fungi, which were invasive into subjacent tissues, and/or bacteria, which were usually superficial. Fungal culture was performed in 3 cases and isolated Fusarium spp ., although fungal morphology varied and multiple fungal species may have been present. Presumptive green algae were associated with ulceration in 1 case with minimal to no inflammation. Presumptive cyanobacteria were identified within a biofilm overlying the gills in 4 of 48 cases and were not invasive. Multifocal, random hepatopancreatitis was identified in 16 of 57 cases, 10 of which were associated with bacteria. Metacercarial cysts were identified in 25 of 61 cases and associated with minimal to no inflammation. Depleted eosinophilic globules in hepatopancreatic interstitial cells were interpreted as decreased nutritional status in 12 of 57 cases.